The effect of plant domestication on the seed microbiome - Soldan, R (2021)
There is a growing body of literature demonstrating the role of microbial communities in plant growth, health, and resilience. It is becoming increasingly clear that advances in our understanding of plant-microbe interactions could make a significant difference in sustainable agricultural production.